2014
DOI: 10.1039/c3dt51764k
|View full text |Cite
|
Sign up to set email alerts
|

Iron catalysed nitrosation of olefins to oximes

Abstract: Fe(BF4)2·6H2O/2,6-pyridinedicarboxylic acid catalysed nitrosation of a wide variety of substituted styrenes has been developed in the presence of t-BuONO/NaBH4 under H2 pressure (10 bar) in MeOH-H2O (5 : 1) to afford corresponding oximes in good to excellent yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…891 The olefins were treated with tert-butyl nitrite and sodium borohydride in a hydrogen atmosphere to afford aryl methyl oximes in high yields.…”
Section: Càheteroatom Bond Forming Additions To Càc Double and Triplementioning
confidence: 99%
“…891 The olefins were treated with tert-butyl nitrite and sodium borohydride in a hydrogen atmosphere to afford aryl methyl oximes in high yields.…”
Section: Càheteroatom Bond Forming Additions To Càc Double and Triplementioning
confidence: 99%
“…245 An iron(II) bis tetrafluoroborate hexahydrate/dipicolinic acid combination served as the metal salt/ligand system. The authors found that a 5:1 mixture of MeOH-H 2 O to be best for this transformation.…”
Section: C-n Bondsmentioning
confidence: 99%
“…Lahiri and Maiti further investigated the reaction, and found that a catalyst combination of iron(II) tetrafluoroborate and dipicolinic acid (119) was also effective for the nitrosation of styrene derivatives (Scheme 26 B). [69] A change in reaction solvent from ethanol to a methanol/water mixture (5:1) also proved effective. Once again a hydrogen atmosphere was found to be beneficial.…”
Section: Iron-catalysed Radical-mediated Hydrofunctionalisationsmentioning
confidence: 96%